PENGARUH PROGRAM DIALOG INTERAKTIF “HALO KALTIM” RADIO REPUBLIK INDONESIA TERHADAP TINGKAT KEPUASAN PENDENGAR - Heriyanto, Eddy Soegiarto K, dan Selviana Meikayanti (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
The growth of the mass media industry in recent years has shown increasingly tight competencies. At first there were only electronic media and print media such as radio, television and newspapers. But now there are online media via the Internet such as websites or web. The development of online media users in Indonesia makes print media, such as radio, should present the best breakthrough for the target audience, to survive in the future.This research is intended to examine the effect of the program quality "Halo Kaltim" to the listener's satisfaction at Radio Republik Indonesia Samarinda. The research was conducted using regression analysis techniques on 88 listeners of the Interactive Dialogue Program "Halo Kaltim".The results showed that program quality had a positive and significant effect on listener satisfaction. This shows that improve the program quality "Halo Kaltim" will increase the listener's satisfaction of the program "Halo Kaltim" Radio Republik Indonesia Samarinda.Radio Republik Indonesia Samarinda is expected to maintain the interactive dialogue program quality "Halo Kaltim" because it has a significant effect on listeners' satisfaction Interactive Dialogue Radio Program "Halo Kaltim" Radio Republik Indonesia Samarinda.